Auxiliary device for preliminary forming of stair steps for duplex house - WEN CHENGUANG; LIN XINWU; LUO JUN; FENG XU (2022)
The auxiliary device comprises a bottom plate, a sliding sleeve, a sliding rod and a top plate, the top of the bottom plate is fixedly connected with the bottom of the sliding sleeve, the bottom of the top plate is fixedly connected with the top of the sliding rod, and the inner wall of the sliding sleeve is slidably connected with the bottom of the sliding rod. Screw holes are formed in the two sides of the top of the bottom plate, a first clamping plate is fixedly connected to one side of the surface of the sliding sleeve, a first square groove is formed in the surface of the first clamping plate, and a second limiting hole is formed in the surface of the sliding rod. According to the auxiliary device for preliminary forming of the stair steps for the duplex house, the problems that most of existing auxiliary devices for preliminary forming of the stair steps for the duplex house are fixed through wood piles, the safety coefficient of the wood pile structures is not high enough, and collapse possibly occurs